A Monoclonal Antibody-Based Immunochromatographic Test Strip and Its Application in the Rapid Detection of Cucumber Green Mottle Mosaic Virus - Zichen Zhao; Yanli Tian; Chang Xu; Yuanfei Xing; Lili Yang; Guoliang Qian; Xiude Hua; Weirong Gong; Baishi Hu; Limin Wang (Biosensors, 2023)
Two specific monoclonal antibodies (mAbs) were screened, and an immunochromatographic strip (ICS) test for rapid and specific detection of cucumber green mottle mosaic virus (CGMMV) was developed. The coat protein of CGMMV was heterologously expressed as an immunogen, and specific capture mAb 2C9 and the detection mAb 4D4 were screened by an uncompetitive immunoassay. The test and control lines on the nitrocellulose membrane were coated with the purified 2C9 and a goat anti-mouse IgG, respectively, and a nanogold probe combined with 4D4 was applied to the conjugate pad. Using these mAbs, a rapid and sensitive ICS was developed. Within the sandwich mode of 2C9–CGMMV–4D4, the test line showed a corresponding positive relationship with CGMMV in infected samples. The ICS test had a detection limit of 1:5000 (w/v) for CGMMV in samples and was specific for CGMMV, with no observed cross-reaction with TMV or CMV.